Pengaruh Profitabilitas, Likuiditas dan Nilai Perusahaan Terhadap Harga Saham Pada Perusahaan Transportasi 2019-2023 - Darmawan, Ricky; Septianus, Nicko; Kardinal (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to examine the profitability variables namely ROA, Liquidity namely CR, firm value namely PBV, on the share price of transportation companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses quantitative methods in sampling in this study using purposive sampling technique. With the sample criteria obtained as many as 31 companies with a period of 5 years. Data analysis using normality test, multicoloniearity test, heteroscedasticity test, autocorrelation test, multiple linear analysis test, determination coefficient test, f test (simultaneous), and t test (partial). The results of this study indicate that simultaneously profitability, liquidity, firm value have a significant effect on stock prices. Partially profitability and firm value has a significant effect on stock prices while liquidity has no significant effect on stock prices